Molecular Characterization of Eimeria Species in Broiler Chickens, Ethiopia - Chere MA; Melese K; Megerssa YC (Veterinary Medicine: Research and Reports, 2022)
Meskerem Adamu Chere,1 Kasech Melese,2 Yoseph Cherinet Megerssa3 1Bio and Emerging Technology Institute, Addis Ababa, Ethiopia; 2Debre-Zeit Agricultural Research Center, Bishoftu, Ethiopia; 3College of Veterinary Medicine and Agriculture, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Meskerem Adamu Chere, Bio and Emerging Technology Institute, Addis Ababa, Ethiopia, Tel +251935963110, Email madchere@gmail.comBackground: Eimeria is a parasitic organism causing coccidiosis, an enteric disease of major economic importance in poultry. The conventional methods for species identification of Eimeria have major limitations.Methods: Fresh fecal samples were randomly collected from 50 small and large-scale commercial broiler farms located in Adama, Bishoftu, Dukem, and Mojo towns. Polymerase chain reaction (PCR)-based assay was used for the differentiation of Eimeria species circulating among study sites and broiler farms. DNA was extracted from Eimeria oocytes using a DNeasy Tissue Kit. The extracted DNA templates and the genus-specific primers (Invitrogen) were used for the amplification of the ITS-1 region from seven Eimeria species of chicken. Descriptive statistical analysis and t-test were used to summarize and analyze the data.Results: The PCR result confirms that all the seven species of Eimeria were detected in both small and large-scale broiler farms. Prevalence variation was found among broiler farms and between study sites. The frequency of E. brunetti (P< 0.006) and E. tenella (P< 0.04) in the small-scale broiler farms was significantly higher compared to that of in large-scale farms. A significantly higher frequency of E. acervulina (P< 0.03) and E. brunetti (P< 0.03) was detected in broiler farms of Dukem and Mojo compared to the broiler farms in Bishoftu. The study also revealed that multiple infections of Eimeria species per sample are common in most farms. Among the evaluated small-scale broiler farms of Bishoftu, 80% showed up to 5 mixed species. In addition, about 33% of large-scale and 20% of small-scale broiler farms showed 6– 7 mixed species.Conclusion: This study characterized all the seven Eimeria species and revealed that multiple infections of Eimeria species per sample are common in most of the evaluated farms. The current findings might be useful for future anticoccidial vaccine development and for effective chemoprophylactic and control strategies.Keywords: broiler chickens, Eimeria, polymerase chain reaction, Ethiopia